1988
DOI: 10.1139/v88-455
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of alkoxide ions following collisional activation. An energy-resolved study

Abstract: . Can. J. Chem. 66, 2947Chem. 66, (1988.The collisionally activated dissociation reactions of the C2 to C5 alkoxide ions have been studied for collisons occurring at 8 keV kinetic energy and also over the range 5 to 100 eV kinetic energy. The alkoxide ions fragment by 1,2-elimination of H2 andlor an alkane. Thus, primary alkoxide ions fragment by elimination of H, only, secondary alkoxide ions show elimination of Hz and alkane molecules, while tertiary alkoxide ions show elimination of alkanes only. In alkan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 19 publications
5
31
0
Order By: Relevance
“…Overall, the fragmentation pathways deduced for lactate (Fig. ) are consistent with the stepwise dissociation process resulting from previous experimental and theoretical mechanistic studies of the gas‐phase, unimolecular decomposition of aliphatic alkoxide ions. Furthermore, energies computed for the formation of the product ions are below the maximum energy transfers to ions of modest masses on collision with argon atoms…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Overall, the fragmentation pathways deduced for lactate (Fig. ) are consistent with the stepwise dissociation process resulting from previous experimental and theoretical mechanistic studies of the gas‐phase, unimolecular decomposition of aliphatic alkoxide ions. Furthermore, energies computed for the formation of the product ions are below the maximum energy transfers to ions of modest masses on collision with argon atoms…”
Section: Resultssupporting
confidence: 85%
“…As a simple initial step in the analysis of a product‐ion spectrum, the recognition of complementary pairs of product ions would pinpoint the site of bond cleavage and indicate proton transfer within an ion‐neutral complex as a dissociative mechanism. Further examples of complementary pairs of product anions are seen upon CID of alkoxide ions …”
Section: Resultsmentioning
confidence: 99%
“…The mechanistic information obtained from these studies has been summarized by Bowie and co‐workers 11, 12. A recent study13 of the low‐energy CID of deprotonated peptides containing H or alkyl α‐groups indicated that more extensive and sequence‐specific fragmentation was observed in low‐energy CID than in high‐energy CID for deprotonated peptides; this result is consistent with earlier studies14–17 of non‐peptide systems which showed more extensive and structure‐specific fragmentation in low‐energy CID of negative ions. Recently, Bowie and co‐workers have carried out extensive studies of the low‐energy CID of larger deprotonated peptides 18–24.…”
Section: Introductionsupporting
confidence: 78%
“…The gas-phase fragmentations of simple and more complex alkoxides have been well studied by both collision activated dissociation (CAD) and infrared multiple photon (IRMP) induced elimination techniques. Hayes et al , investigated extensively the CAD of some simple alkoxides, e.g., ethoxide, propoxide, as well as butoxide, and suggested that the loss of neutral molecular hydrogen (H 2 ) from ethoxide and methane (CH 4 ) from butoxide proceed via a stepwise 1,2-elimination mechanism as illustrated below: Additionally, Raftery and co-workers 3 found that the loss of H 2 from complex alkoxide ions such as Ph(CH 2 ) n O - , where n = 1−5, may occur by similar 1,2-elimination mechanisms.…”
Section: Introductionmentioning
confidence: 99%